INFLUECNCE ORGANIZATIONAL CULTURE, STYLE TRANSFORMATIONAL LEADERSHIP AND MOTIVATION WORK EFFORTS TO IMPROVE PERFORMANCE MILLENNIAL GENERATION EMPLOYEES OF UD. JAWA MADURA - Fatmala, Fika; Abadiyah, Rifdah; andriani, Dewi (Universitas Islam Lamongan, 2024)
This study aims to determine the organizational culture, transformational leadership and work motivation on employee performance. Organizational culture (X1), Transformational leadership (X2),0and work motivation0(X3)0is an independent variable0(X) and performance0employee0as a dependent variable0(Y).0population of the study0this is0employees of UD. Jawa Madura in Sidoarjo totaling 67 people. This study was taken using quantitative methods, data collection techniques in the form of questionnaires. Primary data sources in the form of online questionnaires distributed to respondents. This data analysis technique uses instrument testing, classical assumption testing, multiple linear regression analysis, F test, t test, and R2 determinant coefficient. The results of this study indicate that partially organizational culture does not affect employee performance, transformational leadership does not affect employee performance, and work motivation has a significant positive effect on employee performance at UD. Jawa Madura.